Didactic methodology in professional e-sport training. An international experience in Brawl Stars (Metodología didáctica en entrenamiento profesional de e-sport. Una experiencia internacional en Brawl Stars) - Millán Brea Castro (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The impact of eSports today is undeniable. Millions of connected players, international competitions with succulent economic awards, diversity of platforms to participate or track the competitions. A new system of youth socialization, channelled through video games, in which the competition requires a complete sport training. This article describes the methodological strategies for teaching and learning eSports from a semi-professional team. The analysed categories are: training type and schedule, used tools and typology of feedback carried out for the automation of playing behaviours. The research is carried out using a qualitative approach. The data collection is done through semi-structured interviews with the members of the semi-professional QLASH eSports team. The data were coded to simplify the interpretation and the subsequent description. In conclusion, we can point out that the training methodology in eSports has similarities with classic sport, but it does not have a structured and does not follow specific guidelines when executed by the coaches. There are three types of training which usually last approximately one hour and half per day. We cannot confirm that the didactic strategies used during training will improve results during the competition.